Julius caesar: New critical essays - Edited by Zander, Horst (New York Routledge, 2005)
First published in 2005. Routledge is an imprint of Taylor & Francis, an informa company. Horst Zander is Professor of English at the University of Munich.
Keywords: New Critical Essays